Project performance and the effects of human activity: a case study of the University of Salford (International Journal of Scientific Research and Management (IJSRM), 2023)
Conflict is common in the project management industry. Project performance may be impacted negatively or favourably by human activities such as competing interests among stakeholders, project team members, and project managers, as well as by the intimidating methodology and structure of the project management process. This case study at the University of Salford looked into how human activity affects project management and performance. The mixed methodology used in this study allowed for a deeper understanding of the real-world experiences of the subjects and project teams. Project management students and professionals from the University of Salford provided the data, which was collected. The survey generated a sample size of 40 responses, of which 37 were reliable enough for analysis. At the University of Salford, it was discovered that relationships among team members were a crucial human activity that promoted cooperation, trust, and the extension of trust to others, thereby reducing conflict and ties of trust between stakeholders and project managers. However, positive team dynamics and strong group cohesion are required to actively and purposefully encourage conflict in order to achieve the project’s aim, goals, and deliverables. Conflict in project performance and project management productivity, for example, may be reversed. Therefore, to achieve high performance and productivity, the project management process needs strong communication, positive team dynamics, and an understanding of scope. Conflict can have a negative effect on the process, lowering productivity and performance. Project managers should develop their communication skills to avoid this because it is a soft skill that can be learned and enhanced. This guarantees proper coordination, awareness of all stakeholders, and a decrease in conflict.